Sensory Properties of Fermented Blends of Sunflower Press Cake and Whey - Harald Rohm; Sophie Morejón Caraballo; Ana Salvador; Sofia Mendo; Empar Llorca; Stefano Cattaneo; Ivano De Noni; Susanne Struck; Roberto Foschino; Isabel Hernando (Foods)
Sustainability in the food chain and the prevention of food losses is an issue of increasing importance. There is a large number of processing by-products where innovative strategies are helpful for transferring these losses into a consumable state. In a step-by-step approach, this current study focused on the sensory properties of blends of sunflower press cake and whey, fermented with different consortia of microorganisms and intended for being used as a basis for a savory spread. In the first part of the work, blends fermented with six co-cultures from lactic acid bacteria and yeasts were characterized by free choice profiling and quantitative descriptive analysis. The respective results were used to modify the formulation and to select the fermentation cultures that were promising from a sensory point of view. Subsequent investigations allowed reducing sample dimensionality further, and the study was concluded by affective hedonic tests and a check-all-that-apply set-up performed by consumers. The final experiment also comprised a just-about-right approach performed for specifically evaluating spreadability. The outcome of the entire study indicates that it is possible to tailor attractive foods from by-products, provided that the need for final optimizations regarding palatability is considered.